Artisanal and small-scale mining activities as post-mining land use in abandoned mine sites: a case of Giyani and Musina areas, Limpopo Province of South Africa - Sphiwe Emmanuel Mhlongo; George Oluwole Akintola (Brawijaya University, 2021)
South Africa has many artisanal and small-scale mining (ASM) activities that some are registered and others informal and illegal. This paper presents an overview of ASM operations in the vicinity of abandoned mine sites found in Giyani and Musina areas, Limpopo Provine of South Africa. It looks at the mining processes, environmental problems, and health and safety risks of ASM in the area. It also provideds a discussion of practical ways of dealing with the problems of artisanal and small-scale mining operations in a harmonized way with the rehabilitation of the abandoned mine sites. The exploitation of waste rock dumps for aggregate production in Musina demonstrated that formalized ASM activities can be the best alternative uses of the abandoned mine sites. However, artisanal gold mining around Giyani revealed the health and safety risks and environmental problems of these operations. The artisanal gold mining activities worsened the health and safety and the environmental problems of the abandoned mine sites. Therefore, this paper recommends that the efforts of coming up with strategies to formalize and regulate artisanal mining in South Africa be deepened for these activities to be accepteble as sustainable as post-mining land-uses in abandoned mines.